3D Generalized Inverse Beamforming in wind tunnel aeroacoustic testing: application to a Counter Rotating Open Rotor aircraft model. (June 2020) - Zamponi, R.; Chiariotti, P.; Battista, G.; Schram, C.; Castellini, P.
Abstract: Inverse methods are gaining relevance in the aeroacoustic community for their capability to accurately localize and quantify noise sources. Indeed, since modern aircraft are more targeted to the reduction of fuel consumption, and very often some design choices, like Open Rotor (OR) propulsion systems, cause excessive acoustic emissions, accurate knowledge of noise source locations is of fundamental importance. This paper describes the use of an inverse method, namely Generalized Inverse Beamforming (GIBF), to characterize a Counter Rotating Open Rotor (CROR) installed on a 1/7th scale aircraft model. The model was tested in a large Low-Speed Wind Tunnel (WT) at The Pininfarina Aerodynamic and Aeroacoustic Research Center in Turin, Italy, within the framework of the FP7 EU Clean-Sky WENEMOR (Wind tunnel tests for the Evaluation of the installation effects of Noise EMissions of an Open Rotor advanced regional aircraft) project. With respect to previous works already published, the pros and cons of 3D GIBF formulation will be discussed on data collected from an industrial test case. A comparison of L 2 and L 1 norm formulations, as well as multiplicative approach and single array processing in 3D GIBF, will be performed, discussing their differences in terms of source localization accuracy. Since a quantitative analysis on real data cannot be provided because of confidentiality issues, the capability of the present approach to correctly quantify the source strength will be evaluated by considering a synthetic monopole source emitting white noise at different signal-to-noise-ratios (SNRs). Finally, it will be shown that 3D GIBF can provide engineers with more reliable data regarding the acoustic behavior of CROR-based aircrafts, this proving the advantages in exploiting this inverse method in WT aeroacoustic applications.